Ex Vivo and in Vivo Administration of Fluorescent CNA35 Specifically Marks Cardiac Fibrosis - Sanne de Jong; Lars B. van Middendorp; Robin H.A. Hermans; Jacques M.T. de Bakker; Marti F.A. Bierhuizen; Frits W. Prinzen; Harold V.M. van Rijen; Mario Losen; Marc A. Vos; Marc A.M.J. van Zandvoort (Molecular Imaging)
Cardiac fibrosis is a major hallmark of cardiac diseases. For evaluation of cardiac fibrosis, the development of highly specific and preferably noninvasive methods is desired. Our aim was to evaluate CNA35, a protein known to specifically bind to collagen, as a specific marker of cardiac fibrosis. Fluorescently labeled CNA35 was applied ex vivo on tissue sections of fibrotic rat, mouse, and canine myocardium. After quantification of CNA35, sections were examined with picrosirius red (PSR) and compared to CNA35. Furthermore, fluorescently labeled CNA35 was administered in vivo in mice. Hearts were isolated, and CNA35 labeling was examined in tissue sections. Serial sections were histologically examined with PSR. Ex vivo application of CNA35 showed specific binding to collagen and a high correlation with PSR (Pearson r = .86 for mice/rats and r = .98 for canine; both p < .001). After in vivo administration, CNA35 labeling was observed around individual cardiomyocytes, indicating its ability to penetrate cardiac endothelium. High correlation was observed between CNA35 and PSR ( r = .91, p < .001). CNA35 specifically binds to cardiac collagen and can cross the endothelial barrier. Therefore, labeled CNA35 is useful to specifically detect collagen both ex vivo and in vivo and potentially can be converted to a noninvasive method to detect cardiac fibrosis.